The Clinical Symptom and Anatomical Pathology of Tolaki Chicken which Infected Newcastle Disease Viral - Pagala, M. A.; Muladno, Muladno; Sumatri, C.; Murtini, S. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
This study aim was observatiion the clinical and anatomic pathology Tolaki chicken infectedÂ virus Newcastle Disease (ND) as an affirmation analysis of the cause of the viral disease. A total of 30Tolaki chickens divided into 3 groups based on the Mx (Myxovirus) gene genotype. Mx gene is a genethat is antiviral, producing three genotypes (AA, AG and GG), respectively 10 chicks kept in separatecages. Challenge test performed by infection with a virus gene ND VII eye drops at a dose of 104CLD50 /0.5 ml / head. The results showed that in the first week of chicken genotype AA, AG and GGgenerally show the same clinical symptoms such as ducking, breakaway, face swollen, snoring.Chicken looks decreased appetite and green diarrhea are found in the feces. The number of chickensthat died at the AA and AG there are three tails, while the GG Chicken found 6 tail. In the secondweek the AA genotype was not found green diarrhea, while the AG and GG discovered greendiarrhea. The number of chickens that died at the AA and AG there are two tails, while GG was founddead three tails. Total chickens that died at the AA and AG found as many as 5 tails, while the GG asmany as 9 tails. Generally the infected chicken ND virus causes swelling of the spleen,bleeding/redness of the intestine and trachea in all genotypes. Swelling of the spleen in the AAgenotype was found to be 20%, AG and GG 60% of 100%. Spleen were obtained blackish color on theGG genotype of 44.44%. Based on changes in anatomic pathology in this study was obtainedcharacteristics ND diseased chickens, so the chickens have been infected with the virus diagnosedND. Patognomosis changes in anatomical pathology characterized by hemorhagi enteritis in thegastrointestinal tract (gut) and respiratory tract (trachea). Based on the results of the ND viruschallenge test to prove the group challenged chickens have been infected with ND virus. ND virusinfection attacks the intestinal organs, trachea, and spleen affecting the decline of the immunesystem in all genotypes. AA and AG genotypes have better protective properties against ND virusinfection than genotype GG.Key Words: Clinical Symptom, Anatomy Pathology, Tolaki Chicken, and ND Viral